To simplify the expression \( \frac{3^{5}}{3^{-9}} \), you can use the Property of Negative Exponents and the Product Rule of Exponents.
Breakdown:
-
Property of Negative Exponents:
- Recall that \( a^{-b} = \frac{1}{a^b} \). Thus, \( 3^{-9} = \frac{1}{3^9} \).
- However, you can also rewrite \( \frac{1}{3^{-9}} \) as \( 3^{9} \) which helps in the next step.
-
Product Rule of Exponents:
- The rule states that \( \frac{a^m}{a^n} = a^{m-n} \).
- Applying this to our expression \( \frac{3^{5}}{3^{-9}} \): \[ = 3^{5 - (-9)} = 3^{5 + 9} = 3^{14}. \]
Conclusion:
Both the Property of Negative Exponents (which allows the conversion from a negative exponent) and the Product Rule of Exponents (which handles the division of exponentials) were used.
Thus, the correct answer is:
the Property of Negative Exponents and the Product Rule of Exponents.